INCREASED VANCOMYCIN MINIMUM INHIBITORY CONCENTRATION (MIC) AMONG MRSA ISOLATES IN A TERTIARY CARE HOSPITAL - B., Asha Pai K.; N., Sweetha N.; H., Sanjeev; R., Rekha; K., Vimal K.; R., Ganesh H. (Journal of Health and Allied Sciences NU, 2013)
Introduction:Methicillin Resistant Staphylococcus aureus (MRSA) is not only an important nosocomial pathogen but also an incipient community pathogen in many geographical areas. Recommended therapeutic agent for treatment of MRSA infections are glycopeptides, in particular vancomycin. The distribution of vancomycin Minimum Inhibitory Concentration (MIC) values among MRSA isolates in our hospital is unknown. We conducted this study to Determine the distribution of vancomycin MIC values among MRSA isolates from clinical samples in our hospital.Material and Methods:Fifty six MRSA isolates were included in the study. These isolates were obtained from different clinical samples received in the department of Microbiology over a period of six months from august 2012 to January 2013. Screening for MRSA was done by disc diffusion method using Cefoxitin disc. Determination of vancomycin MIC of all the isolates was done by macro broth dilution method.Results:All 56 isolates were sensitive to vancomycin. Out of the 56 isolates tested, 25 (44.64%) and 12 (21.4%) had Vancomycin MIC of 1μg/ml and 2 μg/ml respectively.Conclusion:The high vancomycin MIC values observed among our strains are a cause of concern, as this may have an impact on the success of treatment with vancomycin.
Keywords: Methicillin Resistant Staphylococcus aureus; vancomycin MIC